Alban Berg: The Man and the Work - Carner, Mosco 1904-1985 (New York Holmes & Meier, 1983)
In this book, published with the approval of Berg's widow, Dr. Carner follows his biography with a close analysis of Berg's works one by one. Dr Carner makes much of the long and fruitful relationships in Vienna and Berlin between Berg and his teacher Arnold Schonberg (1874-1951), adding greatly to our knowledge by extensive quotation from the largely unpublished Berg-Schonberg correspondence.
Originally published in 1975
Keywords: Berg, Alban -- 1885-1935; 20th Century (1901-2000); Composer; Biography; Vienna (Austria)